RESPON PASAR ATAS PENGUNGKAPAN EMISI KARBON DI INDONESIA : BAGAIMANA PERAN TATA KELOLA PERUSAHAAN? - Amrie Firmansyah; Pramuji Handra Jadi; Wahyudi Febrian; Eta Fasita (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
Positive responses from investors indicate the company's success in providing information to the public. It reflects the stock prices increase in the capital market. Information that is responded to positively provides investor confidence that it contains decision-making usefulness, and managers can ensure its sustainability in the future. This study aims to examine the association of carbon emissions disclosure with firm value in Indonesia. In addition, this study also examines the role of corporate governance in the association between carbon emissions disclosure and firm value. This study employs secondary data sourced from financial statements available at www.idnfinancials.com and stock price data from www.finance.yahoo.com. The sample employed in this study is a manufacturing company from 2016 to 2019. By using purposive sampling, the sample obtained in the study is 260 observations. The data were analyzed using multiple linear regression for panel data. This study concludes that the carbon emissions disclosure is negatively associated with firm value. In addition, corporate governance has not succeeded in strengthening the positive effect of carbon emission disclosures on firm value. This study suggests that the Indonesia Financial Services Authority (OJK) should re-examine the regulation on sustainability disclosure, which includes carbon emissions, which is one of the current dynamic issues in the world. In addition, companies need to improve the quality of disclosure of information related to sustainability to the public.